2000
DOI: 10.1006/abbi.1999.1546
|View full text |Cite
|
Sign up to set email alerts
|

Anomeric Specificity of Human Liver and B-cell Glucokinase: Modulation by the Glucokinase Regulatory Protein

Abstract: The anomeric specificity of thé wild-type recombinant forms of human liver and B-cell glucokinase was investigated using radioactive anomers of D-glucose as tracers. With D-glucose at anomeric equilibrium and at 30°C, thé maximal velocity, Hill number, and K, amounted, respectively, to 16 /.unol min"1 mg"1,1.8 and 6.9 mM in thé case of liver glucokinase, and 7. The anomeric specificity of liver and pancreatic islet glucokinase was examined by several investigators (1-5). Interest in this matter is motivated in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 50 publications
0
4
0
Order By: Relevance
“…This process can also be reversed by glucose-6-phosphatase (G6Pase) (Figure ). It was found that the hydroxyl group (−OH)-determined stereochemical structure has a great effect on these enzymatic processes. , For example, GK, HK, and G6Pase all show obvious anomeric specificity, where the phosphorylation rate generally takes preference to the β anomer (equatorial hydroxyl group at C1) over α one (axial hydroxyl group at C1). In the next transformation from G6P to G1P, the transfer of the phosphate group from C6 to C1 is catalyzed by phosphoglucomutase (PGM), and αG1P is formed specifically by α-PGM (αPGM) (Figure ). In this process, only the gg rotamer of G6P (the dihedral angle O5–C5–C6–O6 is about −60°) is identified by αPGM during the reaction. , When αG1P is converted back to G6P, the stereochemistry of the C2–OH group becomes an important factor in substrate recognition, , for which the equatorial hydroxyl group at C2 shows specific contacts with αPGM but the axial one does not.…”
Section: Introductionmentioning
confidence: 99%
“…This process can also be reversed by glucose-6-phosphatase (G6Pase) (Figure ). It was found that the hydroxyl group (−OH)-determined stereochemical structure has a great effect on these enzymatic processes. , For example, GK, HK, and G6Pase all show obvious anomeric specificity, where the phosphorylation rate generally takes preference to the β anomer (equatorial hydroxyl group at C1) over α one (axial hydroxyl group at C1). In the next transformation from G6P to G1P, the transfer of the phosphate group from C6 to C1 is catalyzed by phosphoglucomutase (PGM), and αG1P is formed specifically by α-PGM (αPGM) (Figure ). In this process, only the gg rotamer of G6P (the dihedral angle O5–C5–C6–O6 is about −60°) is identified by αPGM during the reaction. , When αG1P is converted back to G6P, the stereochemistry of the C2–OH group becomes an important factor in substrate recognition, , for which the equatorial hydroxyl group at C2 shows specific contacts with αPGM but the axial one does not.…”
Section: Introductionmentioning
confidence: 99%
“…The experimental conditions used in this study to assess the anomeric specificity of the effect of D-glucose upon the phosphorylation, metabolism, and insulinotropic action of D-fructose were selected to minimize the interconversion of the D-glucose anomers (6).…”
Section: Discussionmentioning
confidence: 99%
“…The effects of the two anomers of D-glucose upon D-[U- 14 C]fructose conversion to 14 CO 2 and 14 C-labeled acidic metabolites and upon the cationic and insulin secretory responses to D-fructose were also examined in isolated rat pancreatic islets. The experiments were conducted over 10 min of incubation at 25°C (D-fructose phosphorylation), 60 min of incubation at 4°C (D-fructose metabolism in islets) or with D-glucose anomers maintained for 90 min or less at 4°C (perifused islets) to minimize the interconversion of the glucose anomers (6). Under these conditions, the fraction of ␣-D-glucose converted to ␤-D-glucose, expressed relative to the equilibrium value, is close to 5.4 and 9.0% after 60 and 90 min of incubation at 4°C and to 17.8% after 10 min incubation at 25°C (6).…”
mentioning
confidence: 99%
See 1 more Smart Citation